The early Iron Age metal hoard from the Al Khawd area (Sultan Qaboos University), Sultanate of Oman - Ğawharī, Nāṣir Saʻīd ʻAlī al-; Yule, Paul (Sultanate of Oman, Ministry of Heritage and Tourism, 2021)
Numerous metallic artefacts, deposited in a hoard in ancient times, came to light by chance on the campus of the Sultan Qaboos University in Al Khawd, Sultanate of Oman. Mostly fashioned from copper, these objects compare well with numerous documented artefact classes from south-eastern Arabia assigned to the Early Iron Age (1200-300 BCE)
Also issued in print: 2021
Published by Archaeopress Publishing in association with the Ministryo of Heritage and Tourism, Sultanate of Oman
Includes bibliographical references and index
Zielgruppe: Specialized
Keywords: Oman -- Antiquities; Al- Khawd